Health risk assessment of Staphylococcus aureus and Salmonella from the consumption of street foods in Ethiopia - Mathewos Moges; Ernst Kristian Rodland; Argaw Ambelu (BMC Infectious Diseases)
Abstract Introduction Due to inadequate hygienic practices and improper handling, street foods may become contaminated, posing a significant risk for various foodborne diseases. This study aimed to determine the health risks to consumers from consuming street foods contaminated with Staphylococcus aureus and Salmonella. Method A cross-sectional study design was used from December 2022 to February 2023 on the street foods of Addis Ababa, Hawassa, Dire Dawa, and Jimma towns. A total of 525 street foods were taken from 175 street food vending stalls. A stratified sampling technique was used to select vending stalls. A questionnaire was used to collect the data which were analyzed via SPSS-25. Food samples were analyzed at the Ethiopian Public Health Institute food microbiology laboratory using the standard microbiological methods used for the isolation, enumeration, and identification of bacteria. A quantitative microbial risk assessment was used to assess and determine the risk of infection using a deterministic approach. Result The frequent, average, and occasional consumers of street foods were 26.9%, 52.6%, and 20.5% respectively. The prevalence of Staphylococcus aureus was 43.4% whereas 25.7% for Salmonella species. The risk of infection from S. aureus was higher than Salmonella. The mean annual risk of S aureus infection of consumers was 100%, 99%, and 93% for frequent, average, and occasional consumers respectively. A total of 32.6% of the sampled foods had greater than 104 CFU/g a colony count of Staphylococcus aureus whereas in 25.7% of the samples Salmonella exceeded the safety standards and made the food unfit for consumption. Conclusion The results highlighted the significant risk of infection with Staphylococcus aureus and Salmonella in Ethiopian street foods, and revealed that frequent consumption of street foods was associated with a high risk of infection. This urges improved hygiene practices to mitigate hazards and protect public health.